The outsider ebook - Davidson, Danica (Minecraft: Official Novels, 2023)
Uncover the truth hidden at the heart of a wondrous city in this official Minecraft novel! Jeremy has never brewed a single potion, but he knows what it’s like to be invisible. He lives in the biggest city in the Overworld, surrounded by tall buildings, redstone wonders, and tons of people. So why does he feel so lonely? Why is it so hard to find a friend?   When Jeremy’s family meets a family from out in the wilderness, it looks like it’s going to be the same old story. The outsiders’ kid, Valda, acts like Jeremy is a helpless little baby. Sure, he’s never caught a fish or fought a hostile mob, and maybe school only lets him read about crafting and never try it himself. That doesn’t mean Valda has to be so rude!   But that’s not the only trouble Valda’s family has brought with them. They share a terrifying story: A new kind of zombie has appeared, one that can do things no zombie should be able to do—steal resources and work together to terrorize the folks who live outside The City’s walls.   To stop them, Jeremy and Valda will need to put aside their differences, team up, and learn from each other’s cultures—or the Overworld may never be the same!